PALLAVA ELEMENTS IN SOUTH AND SOUTHEAST ASIAN ART – VISUAL APPRAISAL - Rajarajan, R.K.K.; Rajarajan, Jeyapriya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
It is a known fact that contact between the Tamil country and Southeast Asia, including Śrī Laṅkā and China was a long-established tradition. References to the yavanas in Tamil Caṅkam literature and the notes supplied by Greek, Roman, and Egyptian classical authors would establish the fact that commercial intercourse between the east and west was an immemorial process 1, datable to at least a few centuries earlier than the Christian era 2. However, it was under the Pallavas and Cōḻas that the arts of the country made a daring intrusion into the distant lands 3. In this process of sharing artistic idioms from the subcontinent, the Āndhras of the Amarāvati School, the Guptas, and the Pālas of Beṅgal played a vital role. The Pallava link with the Malaya peninsula was blood-based because a collateral branch of the family is said to have ruled the distant land under Hiranyavarmaṉ whose son Nandivarmaṉ Pallavamalla (731-96 CE) became the ruler of Kāñci when there was no direct male heir to occupy the throne after the premature death of Parameśvaravarmaṉ II (Minakshi (1941), Subramaniam (1967) 80-94).